Odpowiedzi

Najlepsza Odpowiedź!
2010-01-25T16:08:38+01:00
A) (-3)*0,2=-0,6
b) 6*(-⅓)=-⁶/₃=-2
c) (-1,3)*(-2)=2,6
d) (-9)*(½)=-⁹/₂=-4½
e) (-²/₇)*⁷/₁₂=-⅙
f) (-12):6=-2
g) (-4):(-8)=4:8=⁴/₈=½
h) 3,2:(-2)=-1,6
i) (-¾):¼=(-¾)*⁴/₁=-³/₁=-3
j) (-100)*⁸/₂₅=-4*⁸/₁=-32
2010-01-25T16:10:54+01:00
A) (-3)*0,2 = - 0,6
b) 6*(-1/3) = -6/3 = - 2
c) (-1,3)*(-2) = 2,6
d) (-9)*(1/2) = -9/2 = - 4,5
e) (-2/7)*7/12 = - 14/84 = - 2/7
f) (-12):6 = - 2
g) (-4):(-8) = 1/2
h) 3,2:(-2) = - 1,6
i) (-3/4):1/4 = - 12/4 = - 3
j) (-100)*8/25 = - 800/25 = - 32








2010-01-25T16:13:26+01:00
A)0,6
b)-3
c)2,6
d)-4,5
e)-1/4
f)-2
g)0,5
h)1,6
i)-3
j)-32